Investigation into the dynamic visual acuity of skilled cricketers using a continuous motion task - Kelly, R.; Roberts, J. W. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Great demands are imposed upon the perceptual-motor system when undertaking ball-throwing and -hitting tasks including cricket. That is, performers must detect and resolve object details while on the move - something referred to as dynamic visual acuity (DVA). The present study aimed to investigate DVA in skilled cricketers and non-cricketers using a more immediate or real-time assessment. METHODS: Skilled cricketers and non-cricketers had to detect the presence of the gap within a Landolt-C ring as it moved horizontally or vertically, while progressively increasing the size until the participants registered a response. Measures were taken as the mean (dynamic) minimum angle of resolution of the object size at the moment that participants correctly responded to the gap. Objects would move at either a high, medium or low velocity. RESULTS: There was greater dynamic visual acuity in the skilled cricketers compared to non-cricketers (P<0.05). There was a reduced negative influence of object velocity on dynamic visual acuity in the skilled cricketers compared to non-cricketers (P<0.05). CONCLUSIONS: We suggest these findings contribute to the growing evidence surrounding DVA within ball-throwing and -hitting sports, while making some assertions as to the implications for the cricket performance setting.